Studi Komparatif Kesejahteraan Material Anak Panti Asuhan Sebelum dan Masa COVID-19 - Amalia Nurlina; Ihsana Sabriani Borualogo (Jurnal Riset Psikologi, 2021)
Abstract. This Study has purpose to compare the material well being of orphanage children in Bandung before and during COVID-19 pandemic. The participan in this study were children and adolescent aged 10-18 years old (N=89,64% girls; 36% boys). Data collection was using cluster random sampling technique. The measuring instruments used were CW-SWBS (Children's Worlds Subjective Well-Being Scale) and CW-MWBS (Children's Worlds Material Well-Being Scale). Data analysis was performed using paired t test, descriptive statistics using crosstabs and frequencies. Aspects that were seen from material welfare were material deprivation, family economic status, and subjective material well being on the frequency of worrying about the amount of money and food availability. The COVID-19 pandemic had made a decline of all sectors. This situation could certainly affect the material welfare of the orphanage children. The results of this study explain that before the COVID-19 pandemic there were 85.4% of children and adolescents in orphanages who experienced material deprivation. Meanwhile, during the pandemic, the number of children who reported experiencing material deprivation was lower, namely 69.7% of children and adolescents in orphanages. With these results, it shows that during the COVID-19 pandemic there was a decrease in children's appreciation of material deprivation of Orphanage's children in Bandung city. Abstrak. Penelitian ini bertujuan untuk melihat perbandingan kesejahteraan material anak di panti asuhan Kota Bandung sebelum dan masa pandemi Covid-19. Partisipan penelitian ini adalah anak dan remaja Panti Asuhan yang berusia 10-18 tahun (N= 89; 64% anak perempuan, 36% anak laki-laki). Pengambilan data menggunakan teknik sampling cluster random sampling. Alat ukur yang digunakan adalah Children’s Worlds yaitu CW-SWBS (Children's Worlds Subjective Well-Being Scale) Children’s world dan CW-MWBS (Children's Worlds Material Well-Being Scale) Children’s world. Analisa data yang dilakukan menggunakan paired t test, descriptive statistic menggunakan ,crosstabs dan frequencies. Aspek yang dilihat dari kesejahteraan material yaitu material deprivation, family economic status, dan subjective material well being pada frekuensi rasa khawatir terhadap jumlah uang dan memiliki makanan dan minuman setiap hari. Pandemi COVID-19 menjadikan semua sektor mengalami penurunan termasuk sektor Panti Asuhan. Keadaan ini tentunya dapat mempengaruhi kesejahteraan material yang dimiliki anak Panti Asuhan. Hasil dalam penelitian ini menjelaskan keadaan sebelum pandemi COVID-19 anak dan remaja Panti Asuhan melaporkan sebanyak (85.4%) anak dan remaja Panti Asuhan mengalami material deprivation. Namun saat masa pandemi anak yang melapor mengalami material deprivation lebih rendah sebanyak (69.7%). Dengan hasil demikian menunjukan bahwa pada masa pandemi COVID-19 terjadi penurunan penghayatan anak mengenai material deprivation di Panti Asuhan Kota Bandung.